ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MA - Pipit Pitriyani; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze student errors in solving the problems of mathematical understanding ability. This study uses a descriptive method with qualitative approach. The subjects in this study were 28 students of class X in one of the MA in Bandung Barat Regency. This study obtained results, namely the lowest percentage found in question number 2 with instrumental understanding as much 48.33% and in question number 4 with a relational understanding as much 47.86%. Based on the mistakes made by students, the students' abilities in instrumental understanding and relational understanding are still relatively low, as seen from the many mistakes made by students in solving the test questions of mathematical understanding ability.